World Economic Outlook, April 2009 : Crisis and Recovery. (World Economic Outlook; World Economic Outlook ;, 2009)
This edition of the World Economic Outlook explores how a dramatic escalation of the financial crisis in September 2008 provoked an unprecedented contraction of activity and trade, despite active policy responses. It presents economic projections for 2009 and 2010, and also looks beyond the current crisis, considering factors that will shape the landscape of the global economy over the medium term, as businesses and households seek to repair the damage. The analysis also outlines the difficult policy challenges presented by the overwhelming imperative to take all steps necessary to restore financial stability and revive the global economy, and the longer-run need for national actions to be mutually supporting. The first of two analytical chapters, "What Kind of Economic Recovery?" explores the shape of the eventual recovery. The second, "The Transmission of Financial Stress from Advanced to Emerging and Developing Economies," focuses on the role of external financial linkages and financial stress in transmitting economic shocks.